148k views
4 votes
3x + 5 - x = 9x - 7 + 12

1 Answer

4 votes

Answer:Combine like terms

3

+

5

=

9

7

+

1

2

{\color{#c92786}{3x}}+5{\color{#c92786}{-x}}=9x-7+12

3x+5−x=9x−7+12

2

+

5

=

9

7

+

1

2

{\color{#c92786}{2x}}+5=9x-7+12

2x+5=9x−7+12

2

Add the numbers

3

Subtract the same term from both sides of the equation

4

Simplify

5

Subtract the same term from both sides of the equation

6

Simplify

7

Divide both sides of the equation by the same term

8

Simplify

HOPE THIS HELPS :)

Explanation:

User Nassan
by
5.5k points